FACTORS INFLUENCING THE ADOPTION OF MOBILE FINANCIAL SERVICES IN ENHANCING FINANCIAL INCLUSION: USING STRUCTURAL EQUATION MODELING FOR THE DECISION-MAKING APPROACH - BASHIR, BABA KURA; MUHAMMAD, TIJJANI (Innovare Journal of Social Sciences, 2023)
The study aims to examine the relationship between mobile financial services and financial inclusion. Using modification hypotheses related to the technology acceptance model, the theory of Rational Behavior, and the Theory of Planned Behavior were adopted to test hypothesized relationships. The study employed a quantitative approach whereby 220 respondents participated in the survey online, accessing the view on mobile financial services in promoting financial inclusion. Convenience sampling was adopted to select appropriate and needed participants for the study. The study focused on the perception of the mobile users that use mobile banking regarding its usefulness as a banking service. The findings indicate social influence, performance expectancy, risk perception, and trust perception are significantly related to mobile financial services and enhance financial inclusion. The study found that the more mobile banking customers interact with devices, the more mobile financial services grow and accept innovations towards technology and convenient service, and the more likely they are to adopt it. The study contributed significantly to the existing body of knowledge through mobile financial services. The strength of the relationship between mobile financial services and financial inclusion through the independent variables. This provides essential insights and analysis that can influence the outcome of other relationships and the model. A notable limitation is the underestimation of the rural population in this study is significantly important. Future studies should provide larger rural samples of mobile banking users.